The Effectiveness of Graphic Organizer Technique on Student’s Reading Comprehension of Argumentative Text - Suci Dwina Darma; Nanik Nanik (LPPM Politeknik Raflesia, 2025)
This research meant to find out how effective is graphic organizer technique to develop students’ reading comprehension in argumentative text and in what way students can perceive of using graphic organizer technique for contributing learning process. The research was designed by experimental study with 50 students as the samples at second semester students of Stikes Al Fatah Bengkulu. The reading test and questionnaire were using as the instruments of this research. The findings of the research revealed that (1) using of graphic organizers was an effective method to increase students’ comprehensible in reading questions like finding main idea, finding the specific information, making inference, understanding vocabulary and determine references, (2) the students perceived positively responses concerning to use the graphic organizer in learning process.